JUDUL PENELITIAN KUALITATIF - Arifah Elwahdiyah; Zamsiswaya (STKIP Subang, 2026)
A research title is the primary identity of a scientific work, reflecting the focus, objectives, and research approach used. Accuracy in formulating a title is crucial to ensure alignment between the title and the research method. This article aims to examine the concept of qualitative research titles, the characteristics of qualitative research, the differences between qualitative and quantitative research titles, and provide examples of qualitative research titles in the field of education. This research uses a qualitative approach with library research, namely through a review of books and scientific journals relevant to the research title. The results of the discussion indicate that qualitative research titles are descriptive and exploratory, process- and meaning-oriented, and not formulated in the form of statistical variable testing. The main differences between qualitative and quantitative research titles can be seen in the research objectives to be achieved and how the title is formulated. Thus, understanding the characteristics of qualitative research is crucial for researchers to be able to develop research titles that are appropriate, systematic, and in accordance with the approach used.